2007
DOI: 10.1038/labinvest.3700529
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression analysis of formalin-fixed paraffin-embedded tumors

Abstract: RNA expression analysis is an important tool in cancer research, but a limitation has been the requirement for high-quality RNA, generally derived from frozen samples. Such tumor sets are often small and lack clinical annotation, whereas formalin-fixed paraffin-embedded (FFPE) materials are abundant. Although RT-PCR-based methods from FFPE samples are finding clinical application, genome-wide microarray analysis has proven difficult. Here, we report expression profiling on RNA from 157 FFPE tumors. RNA was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
120
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 39 publications
4
120
0
Order By: Relevance
“…The main concern with using routinely prepared/archival FFPET for microarray profiling is that 'block effects', such as pre-fixation time, size of specimen being fixed, formalin/tissue processing conditions and length of time in storage, will have variable effects on RNA degradation and modification rates and consequently adversely affect the reliability and clinical interpretation of microarray data. The impact of 'block effects' on RT -PCR and microarray performance is only just coming to light (Penland et al, 2007;von Ahlfen et al, 2007), but may not be as problematic as feared especially considering that RT -PCR (the gold standard assay for FFPET interrogation) has demonstrated reliable performance despite the presence of these factors. This may also be true for microarray applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main concern with using routinely prepared/archival FFPET for microarray profiling is that 'block effects', such as pre-fixation time, size of specimen being fixed, formalin/tissue processing conditions and length of time in storage, will have variable effects on RNA degradation and modification rates and consequently adversely affect the reliability and clinical interpretation of microarray data. The impact of 'block effects' on RT -PCR and microarray performance is only just coming to light (Penland et al, 2007;von Ahlfen et al, 2007), but may not be as problematic as feared especially considering that RT -PCR (the gold standard assay for FFPET interrogation) has demonstrated reliable performance despite the presence of these factors. This may also be true for microarray applications.…”
mentioning
confidence: 99%
“…This may also be true for microarray applications. In a study of 157 archival FFPET samples aged 2 -8 years, correct classification of tumour type and subtype using an unsupervised approach suggests that biological data are more powerful than 'block effects' (Penland et al, 2007). Furthermore, several groups have compared FT and FFPET arrays in paired and unpaired samples and have shown that archival FFPET specimens can retain valuable and reliable transcript data.…”
mentioning
confidence: 99%
“…Cumulatively, these lead to suboptimal nucleic acid quality and hampered reverse transcription and amplification reactions. [57][58][59][60] Thus, in the past, gene expression profile studies were restricted to tissues with higher intrinsic nucleic acid quality, such as cell lines, fresh blood or fresh frozen tissue. [61][62][63][64][65][66] Recent biotechnological advances have improved RNA isolation and amplification techniques, resulting in successful use of formalin-fixed paraffinembedded tissues to identify gene signatures in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one such samples met the minimal quality pre-requisites for further use, that is, RNA yield of at least 25 ng/ml with OD 260 /OD 280 ratio 41.8, according to criteria slightly more stringent than what previously proposed for similar studies. 16 Such values were set based both on the electrophoretic profile of the starting RNA samples and the results of multiple test DASL assays, where the number of detected genes was taken as parameter for quantitative evaluation of array performance. It is worth noting that, in case of failure, inspection of Hematoxylineosin-stained microphotographs of a section from the same paraffin block helped explain most of the cases with low RNA yield was obtained, as we observed in such cases one or more of the following conditions: (i) small size of the tissue fragment included (o0.5-0.8 cm 2 ); (ii) prevalence in the sample of fat tissue or (iii) presence of large patches of necrotic or fibrotic tissue (data not shown).…”
Section: Application Of Dasl Arrays To Expression Profiling Of Ffpe Bmentioning
confidence: 99%
“…Indeed, given the wide availability of paraffin-embedded tissue blocks dating back several years and including valuable clinical annotation, such as those derived from clinical trials, would provide enough material for large and uniform retrospective studies. Unfortunately, FFPE samples provide in most cases RNA unfit for standard analysis by microarray-based methods, 16 due to extensive RNA degradation by formalin treatment and during storage. 17,18 We tested here the recently developed cDNA-mediated annealing, selection, extension and ligation (DASL) methodology for gene expression profiling of highly degraded human RNA samples, 19,20 applying it to in vitro degraded RNA from human MTs and FFPE MT biopsies.…”
mentioning
confidence: 99%